Model Characteristics of Psychophysiological Indicators of Qualified Kickboxers - Yevhen Myroshnychenho; Yuriy Tropin; Julia Kovalenko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the model characteristics of psychophysiological indicators of qualified kickboxers. Material and methods: analysis of scientific and methodological information, Internet sources and generalization of leading practical experience, psychophysiological research methods, methods of mathematical statistics. The study involved 30 qualified kickboxers who train in Kharkiv sports schools and are members of the Kharkiv Regional Kickboxing Federation WPKA. The participants aged 18 to 22 years old. Athletes are qualified as Masters of Sports and Candidates of Master of Sports. Results: based on the analysis of scientific and methodological information, Internet sources and generalization of best practical experience, it was found that the specifics of competitive activities in martial arts affects the level of psychophysiological reactions that provide high sports results. The evaluation of simple, complex motor reactions and specific perceptions of qualified kickboxers is performed. The results of the study show the homogeneity indicators of simple and complex reactions, as the coefficient of variation is in the range from 5,48 % to 10,07 %, except for the indicator of complex reaction to a moving object that has a high coefficient of variation (26,10 %). Indicators of specific perceptions have a high coefficient of variation (from 14,02 % to 39,01 %). This is due to the fact that specific perceptions reflect, to a greater extent, the individual, genetically determined, characteristic of a particular athlete psychophysiological state. Based on the obtained results, the model characteristics of sensorimotor reactions and specific perceptions of qualified kickboxers are determined. Conclusions: the analysis and the presented models became the basis for the development of evaluation criteria for sensorimotor reactions and specific perceptions of qualified kickboxers. Model characteristics of psychophysiological indicators of qualified kickboxers are developed and can be the basis for the selection of athletes in the formation of the team.